ANALISIS ALUR ANIME BARAKAMON BERDASARKAN TEORI STRUKTURALISME ROBERT STANTON (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study contains a plot analysis of the anime Barakamon based on the theory of structuralism. The problem that will be discussed in this study is the Barakamon anime plot seen from the narrative structure contained in the anime. The purpose of this study is to describe the plot based on the theory of structuralism. The method used in this research is descriptive qualitative method. The data source used in this study is the Barakamon anime by director Masaki Tachibana. The collected data is then described based on Robert Stanton's theory. The steps taken are selecting and determining the object of research, identifying, limiting the subject matter, collecting data, analyzing data and seeking conclusions. Based on this research, the researchers obtained the results, namely in the Barakamon anime, it showed an initial plot, middle plot, and final plot. These auras complement each other so that a complete story is built.Key Words: Analysis, Anime.